Streamline English connections : - Hartley, Bernard (Oxford University Press, 1995)
This book is disigned yo follow on from "Streamline English departures", the emphasis is on oral skills and units of everyday conversation have been included to underline the practical nature of the language being taught. The material consists of 80 units, each unit provides a 50-minute lesson and is clearly laid out on a separate page